Strategi Komunikasi Krisis Jasa Pernikahan untuk Menciptakan Inovasi Berbasis Teknologi - Hildawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The wedding service industry faces major challenges in maintaining its reputation in the digital era, especially in the midst of a crisis that can affect consumer trust. This study discusses the crisis communication strategies implemented by wedding service providers in utilizing digital innovation to mitigate negative impacts and restore public trust. This study uses a qualitative approach with case study analysis on several wedding service providers who have successfully handled the crisis through the use of digital platforms such as social media, wedding applications, and technology-based customer management systems. The results of the study indicate that the success of the crisis communication strategy is greatly influenced by the speed of response, transparency, and the ability to adapt to technological changes. This article provides insights for industry players to integrate digital innovation in crisis management, as well as build a sustainable brand reputation amidst increasingly fierce competition.